Employee resource group excellence grow high performing ERGs to enhance diversity, equality, belonging, and business impact - Rodriguez, Robert (John Wiley & Sons, Inc., 2022)
"Approximately 90% of Fortune 500 companies now have employee resource groups (ERGs). Some have had ERGs for over 30 years. Other companies are just launching their employee resource groups. Organizations with ERGs tend to have between 6 to 8 of them. When organizations have ERGs, their minimum target is to get at a minimum of 10% of their employee population belonging to an ERG. Some companies have ERGs that are quite established in an organization to the point that they have about 40% of their employees belonging to one ERG. Yet even though ERGs are quite prevalent in corporate America, most companies struggle to expand the value proposition of their ERGs beyond them being viewed as the "food, flag and fun" groups. This reputation has been established because ERGs often focus on social events, networking activities, community outreach and cultural celebrations. These aspects are important, but ERGs remain an under-utilized business asset. Also, while companies try to leverage their ERGs as a mechanism to groom future leaders, ERGs are not a destination for existing leaders within a company. This book includes an exhaustive look at the current state of employee resource groups in corporate America. The authors leverage their extensive experience in consulting with over 300 companies with their ERG initiatives to find gaps that need to be closed in order to elevate ERGs to greater value. More importantly, the authors leverage ERG assessment data gleaned from close to 200 corporations to identify key insights, trends and correlations that help to differentiate top tier ERGs from ERGs that have minimum impact. Through first-hand experience, analysis and assessment findings, the authors share their insightful recommendations on how to unleash the potential held within ERGs in corporate America"--